P. LESGAFT'S WORK «SCHOOL TYPES» AS A SAMPLE CHARACTERISTICS OF PUPILS LATE XIX - EARLY XX CENTURY - Mikhno, Oleksandr P. (Educological discourse, 2016)
The article analyzes the typology of pupils characters P. Lesgafta in the theoretical and methodological aspect, define the objectives and principles of its creation, noted the use of pedagogical and psychological terminology, reproduced plan studying a pupil  that is the basis of the description of  types of schoolchildren:  1) family conditions, 2) pupil manifestation in the physical, mental, and moral fields, 3) related to teacher and classmates, 4) predictions about the future of schoolboy, 5) possible correction plan. It was found the practical value of the work "School types", which is  to use  it as a sample for teachers  in the process of studing pupil and compiling his characteristic.